L’entrée des femmes au Parlement britannique : le discours inaugural des députées à la Chambre des Communes (1919-2019) - Karine Rivière-De Franco (Genre & Histoire)
A century after the first woman entered the House of Commons in 1919, female representatives now make up 33% of all Members of Parliament. This paper intends to examine the place and the role of female parliamentarians through the maiden speech which each new member delivers. The speech takes place within a framework of traditions and rules, but it also represents an opportunity for newly elected parliamentarians to highlight specific topics. The study of nearly 500 speeches over a century, through a quantitative and qualitative prism, enables us to assess to what extent female parliamentarians conform to tradition and try to integrate the dominant group or, on the contrary, how far they choose to break with conventions. The analysis also aims at identifying the themes dealt with by the new female MPs and determining if they act as spokespersons for the female British population by focusing on certain issues.